Realitas Citra Politik Tri Rismaharini - Ali Sahab (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Tri Rismaharini (Risma) is the Mayor of Surabaya who had successfully led Surabaya during the period of 2010-2015. In 2015 mayoral election, Risma was re-elected as the Mayor of Surabaya. Risma has been known as a mayor who really concerns about environment. During her first tenure, Risma had built many city parks, successfully improved beauty of Surabaya. Such leadership style had attracted the public. In addition, Risma had become a media darling in both printed and electronic media, locally and nationally. This research used survey to capture society's perception toward the leadearship of Risma during 2010-2015. Sample were collected from group leaders and society in general. There are 50 opinion leaders samples consists of academician, businessmen, artist, religious leader, non-governmental organization, politician, and mass media. This research concludes that Risma had successfully constructed her image as a good mayor by conducting populist programs to attract more public attentions than carrying out substantial programs to solve crucial problems as public priorities and needs. It indicates that Risma insisted to frame herself as a caring and lovely leader. In fact, Risma had often become less powerful against the intervention of business persons who had capital strength in Surabaya, East Java, Indonesia.